The Impact of the Best Speaker Program and Students’ Learning Interest on Arabic Speaking Skills - Saleh, Ummu Sulaimah; Abidin, Munirul (LP2M IAIN Sultan Amai Gorontalo, 2024)
The best speaker program and interest in learning have a significant influence on improving Arabic speaking ability. This study analyzes the effect of the best speaker program and interest in learning Arabic on students' speaking ability at the Naatiq course institution. This research is Quantitative research with a type of research in the form of correlational research, namely to measure the relationship between the implementation of the best speaker program (X1) and interest in learning (X2) on students' Arabic speaking ability (Y). Data collection techniques used in this study are questionnaires and speaking ability tests. The data collected is then analyzed using the Pearson validity test, reliability test, and multiple linear regression analysis through the SPSS version 25 statistical program to determine the significance level of each variable's relationship. The results showed that (1) The best speaker program has a positive and significant influence on students' Arabic speaking skills at the Naatiq course institution, (2) Interest in learning Arabic has a positive and significant effect on students' Arabic speaking ability at Naatiq course institution, (3) Simultaneously, the best speaker program and interest in learning Arabic have a positive and significant influence on students' Arabic speaking ability at the Naatiq course institution. This study implies that the implementation of the best speaker program and increased interest in learning can simultaneously significantly improve students' Arabic speaking ability.